Comparative Non-government-based Cryptocurrencies Policy between Thailand and Argentina - Srirath Gohwong (Journal of Contemporary Governance and Public Policy, 2021)
The objective in this study were to study the state of the art of Non-government-based cryptocurrency public policy in Thailand, to study the state of the art of Non-government-based cryptocurrency public policy in Argentina, to compare non-government-based cryptocurrency public policy between Thailand and Argentina, and to discuss implications for both Thailand and Argentina. Documentary research was employed in this study. The findings showed that Thailand and Argentina used a set of policy instruments and blockchain as a financial innovation in order to promote their political equilibriums. The comparison of non-government-based cryptocurrency public policy between Thailand and Argentina was conducted in four issues – scope, policy instrument, distribution, and restraints and innovation. In addition, both countries used both active and passive measures in order to maintain the stability of their political systems.